Cohort profile: HealthWise Wales. A research register and population health data platform with linkage to National Health Service data sets in Wales. Issue 12 (2nd December 2019) - Hurt, Lisa; Ashfield-Watt, Pauline; Townson, Julia; Heslop, Luke; Copeland, Lauren; Atkinson, Mark D; Horton, Jeffrey; Paranjothy, Shantini
Abstract : Purpose: Recruitment and follow-up in epidemiological studies are time-consuming and expensive. Combining online data collection with a register of individuals who agree to be contacted about research opportunities provides an efficient, cost-effective platform for population-based research. HealthWise Wales (HWW) aims to facilitate research by recruiting a cohort of individuals who have consented to be informed about research projects, advertising studies to participants, supporting data collection on specific topics and providing access to linked healthcare data for secondary analyses. In this paper, we describe the design of the project, ongoing data collection, methods of data linkage to routine healthcare records, baseline characteristics of participants, the strengths and limitations of the register, and the ways in which the project can support researchers. Participants: Adults (aged 16 years and above) living or receiving their healthcare in Wales are eligible for inclusion. Participants consent to be contacted for follow-up data collection and for their details to be used to access their routinely collected National Health Service records for research purposes. Data are collected using a web-based application, with new questionnaires added every 6 months. Data collection on sociodemographic and lifestyle factors is repeated at intervals of 2–3 years. Recruitment is ongoing, with 21 779 participants alive and currently registered. Findings to date: 99% of participants have complete information on age and sex, and 64% have completed questionnaires on sociodemographic and lifestyle factors. These data can be linked with national health databases within the Secure Anonymised Information Linkage (SAIL) databank, with 93% of participants matching a record in SAIL. HWW has facilitated the recruitment of 43 826 participants to 15 different studies. Future plans: The medium-term goal for the project is to enrol at least 50 000 adults. Recruitment strategies are being devised to achieve a study sample that closely models the population of Wales. Potential biosampling methods are also currently being explored.